Papal Bull Print, Politics, and Propaganda in Renaissance Rome - Meserve, Margaret (Book collections on Project MUSE., 2021)
"This work of history examines how the Renaissance popes adopted print as a medium for political discourse in the first decades after the technology's invention (ca. 1470-1520). Drawing on literary and material analyses of dozens of little-known incunabula and early sixteenth-century editions, this study argues that the Renaissance papacy was an early adopter of print and keenly attuned to its political potential"--